PEMODELAN PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS ISU BENCANA UNTUK GURU IPA DI SMP MUHAMMADIYAH MERAUKE - Putra, Don Jaya; Ekasari, Aprilita (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Merauke, as a region with a very large potential for flooding, requires early preparedness, one of which is through the integration of disaster mitigation education into school learning. This community service program aims to improve the capacity of science teachers at Muhammadiyah Merauke Middle School in modelling and implementing Problem-Based Learning (PBL) that utilises Artificial Intelligence (AI) technology, Educafe, and Curipod in the context of disaster issues. The implementation method includes a pretest, intensive training (workshop), independent practice mentoring, and a posttest. The training was attended by 10 teachers (3 science teachers and 7 non-science teachers) and 9 Physics education students from Musamus University as co-facilitators. The pretest results showed that teachers' understanding of disaster-based PBL and the use of AI in learning is still relatively low. The training focused on strengthening the concept of PBL, analysing the disaster context in Merauke, and practising using AI Education platforms such as AI Educafe and Curipod to design LKPD and interactive learning media provided by the AI ??education platform. Post-test results showed significant improvements in teachers' conceptual understanding and technical skills in designing learning. This activity concludes that the hybrid training model (theory, practice, and mentoring) is effective in improving teacher competency. Collaboration with students also creates a mutually beneficial learning ecosystem. Continued mentoring and the development of more contextual digital modules are recommended.